Features property rights of agricultural land (Journal of actual problems of jurisprudence, 2018)
At present, the right to private ownership of land is actively discussed in civil society. To resolve with regard to regulation at the legislative level, the state was proposed by the President of the Republic of Kazakhstan. Since the acquisition of the independence of the Republic of Kazakhstan, the law on the Earth has been adopted, as well as during the development of legal regulation of land issues, the first steps of legal regulation and formation of the system of land relations in one single, holistic were made. The peculiarity of this law is that at present, the application of norms restricting the ownership of land and property in the states-social level is increasingly asserted. Formation and development of public relations in the Republic of Kazakhstan as a sovereign state, namely land relations, meets the requirements of the standards of zakonodatelstva. This socio-economic, political and legal relations in accordance with the requirements for the development of a new life for a young independent state, for themselves and for future generations of our state, regulating the above-mentioned relations again, economic, legal reforms, requires carrying out in accordance with the requirements of life. The main goal, according to the President of the Republic of Kazakhstan in the context of political, economic reforms, especially in the transition period is to ensure stability as a necessary condition for successful implementation. Key words: state, law, society, legislation, property, land, legal regulation, agrarian.